Possessiveness dan Eksistensi Diri sebagai Prediktor Sikap Public Display of Affection Remaja di Indonesia - Scarvanovi, Berliana Widi; Fitriana, Safira Nur; Kusumaningrum, Indah (Personifikasi: Jurnal Ilmu Psikologi, 2025)
The phenomenon of public display of affection (PDA), or the act of expressing affection in public spaces, has become increasingly prevalent among Indonesian adolescents. However, this practice often sparks debate, as Indonesian culture upholds values of modesty and Eastern norms that generally regard public displays of affection as inappropriate. This study aims to examine the contribution of possessiveness and self-existence in predicting public display of affection attitude among Indonesian adolescents. Employing a quantitative approach, the study involved 300 adolescents aged 13–18 years in Indonesia, selected through a cluster sampling technique. The instruments used included the Love Addiction Inventory, the Self-Existential Scale, and a public display of affection attitude scale developed by the researchers. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The findings revealed that possessiveness and self-existence significantly influenced public display of affection attitude, contributing a total of 60%. Furthermore, significant differences were found based on gender in the average scores of the public display of affection and self-existence variables, with male adolescents tending to have higher average scores on both variables. These results provide a basis for developing educational programs on healthy expressions of affection and serve as a reference for further research on the psychological dynamics within adolescent interpersonal relationships.